2011
DOI: 10.1002/ange.201101190
|View full text |Cite
|
Sign up to set email alerts
|

Spin Transition and Exchange Interaction: Janus Visions of Supramolecular Spin Coupling between Face‐to‐Face Verdazyl Radicals

Abstract: Drastisch ist der Einfluss, den das koordinative Binden von Verdazylradikalen an diamagnetische Metallionen auf die Kristallpackung der Träger des Elektronenspins hat. Die Stapelanordnung der beiden Radikale hat ein magnetisches Verhalten zur Folge, das typischer für einen Spinübergang vom Typ S=0→S=1 ist als für die üblicherweise angenommene Austauschwechselwirkung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The experimental curve reaches its maximum value of 0.425 emu K mol −1 at approximately 29 K, whereas our simulations (decamer model) reach a value of 0.420 emu K mol −1 at approximately 37 K. It is worth noting that our work has been carried out using a crystal structure obtained at room temperature, that is, far from the temperature at which the ( χT ) max occurs. It has been reported that this fact might be a source of error in the elucidation of the magnetic topology 4c. 24, 26c However, for the TTTA ⋅ Cu(hfac) 2 crystal, given the quality of our simulated χT ( T ) curves over the whole range of temperatures, it is reasonable to think that the thermal effects may not be important in its magnetic characterization.…”
Section: Resultsmentioning
confidence: 90%
“…The experimental curve reaches its maximum value of 0.425 emu K mol −1 at approximately 29 K, whereas our simulations (decamer model) reach a value of 0.420 emu K mol −1 at approximately 37 K. It is worth noting that our work has been carried out using a crystal structure obtained at room temperature, that is, far from the temperature at which the ( χT ) max occurs. It has been reported that this fact might be a source of error in the elucidation of the magnetic topology 4c. 24, 26c However, for the TTTA ⋅ Cu(hfac) 2 crystal, given the quality of our simulated χT ( T ) curves over the whole range of temperatures, it is reasonable to think that the thermal effects may not be important in its magnetic characterization.…”
Section: Resultsmentioning
confidence: 90%
“…[9] However, some classes of radicals do not suffer from this phenomenon, and magnetic properties are well-established in the solid state. Crossover molecule-based magnetic materials have been reported, [10][11][12][13][14] questioning the relevance of a mere spin-coupled picture using temperatureindependent parameters to rationalize the magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Moreover, a recent study on [CuClA C H T U N G T R E N N U N G (Ovdim)] (Ovdim = 1,5-dimethyl-3-(2'-imidazole)-6-oxoverdazyl) underlined the necessary interplay between temperature-dependent structure determination, magnetic measurements, and theoretical calculations to fully understand the complex magnetic behavior of this family of compounds. [10] We apply this global strategy to the 1:1 adduct of 1,5-dimethyl-3-(2-pyridyl)-6-thiooxoverdazyl (Svdpy) radical and hydroquinone (hq), denoted Svdpy:hq (Figure 1), paying particular attention to the theoretical aspects. In light of previous studies, how much does the heteroatom influence the supramolecular assembly and eventually the magnetic properties is part of the issue we wanted to investigate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong magnetic interactions between verdazyl molecules are observed in cases where the heterocyclic planes of two verdazyls are arranged in a stacked manner, with reduced exchange coupling constants when the planes formed slipped stacks (Figure 1b and c). Accordingly, the strongest interactions were observed in a bis-verdazyl substituted ferrocene, where the stacking in the solid state was brought about by the template effect of the ferrocene moiety (estimated, antiferromagnetic (AF) coupling constant J > 2000 cm -1 ) [16], and in an imidazolyl substituted verdazyl, where efficient stacking was achieved after ligation to a Cu(I) center (calculated J of ~1500 cm -1 at 120 K) [17]. In cases where efficient stacking in the crystalline state occurred, rather strong AF couplings have been observed in purely organic, metal-free compounds as well [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%